Incidence Of Pelvic Girdle Pain in Postpartum Women Undergoing Full Term Normal Vaginal Delivery and Lower Segment Caesarean Section - Mujumdar, Samruddhi P.; Patil, Vinaya (Journal of Neonatal Surgery, 2025)
Background: Pelvic girdle pain is defined as the pain which is felt around the pelvic joints, lower back hips and thighs. Pelvic girdle pain can also occur in conjunction with or exclusively in the symphysis this pain is often associated with decrease in activities such as standing, walking and sitting. The incidence of pelvic girdle pain after delivery is due to the factors like hormonal changes altered biomechanics, and increased joint laxity. procedure: This study was conducted after Ethical Clearance was obtained from Institution ethical committee. According to inclusive criteria total 90 participants were included in this study. Participants were included according to Convenience Sampling method; each participant was assessed by using Posterior Pelvic Pain Provocation Test (P4 Test). result: Two Groups were included, first is postpartum women undergoing full term normal vaginal delivery(FTVD) with 66.67% participants positive for P4 Test and second is postpartum women undergoing lower segment caesarean section(LSCS) with 62.22% participants positive for P4 Test. Conclusion: This study concludes that Full Term Normal Vaginal Delivery (FTVD) Group has more incidence rate of Pelvic Girdle Pain than Lower Segment Caesarean Section (LSCS) Group